ECTRIMS/EAN Guideline on the pharmacological treatment of people with multiple sclerosis. (February 2018) - Montalban, Xavier; Gold, Ralf; Thompson, Alan J; Otero-Romero, Susana; Amato, Maria Pia; Chandraratna, Dhia; Clanet, Michel; Comi, Giancarlo; Derfuss, Tobias; Fazekas, Franz; Hartung, Hans Peter; Havrdova, Eva; et al.
Background: Multiple sclerosis (MS) is a complex disease with new drugs becoming available in the past years. There is a need for a reference tool compiling current data to aid professionals in treatment decisions. Objectives: To develop an evidence-based clinical practice guideline for the pharmacological treatment of people with MS. Methods: This guideline has been developed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology and following the updated EAN recommendations. Clinical questions were formulated in Patients–Intervention–Comparator–Outcome (PICO) format and outcomes were prioritized. The quality of evidence was rated into four categories according to the risk of bias. The recommendations with assigned strength (strong and weak) were formulated based on the quality of evidence and the risk-benefit balance. Consensus between the panelists was reached by use of the modified nominal group technique. Results: A total of 10 questions were agreed, encompassing treatment efficacy, response criteria, strategies to address suboptimal response and safety concerns and treatment strategies in MS and pregnancy. The guideline takes into account all disease-modifying drugs approved by the European Medicine Agency (EMA) at the time of publication. A total of 21 recommendations were agreed by the guideline working group after three rounds of consensus. Conclusion: The present guideline will enable homogeneity of treatment decisions across Europe.